Effects of Environmental Parameters on Hydrogen Production of Strain Clostridium beijerinckii CB3 Isolated in North of Vietnam under Anaerobic Condition - Hue, Nguyen Thi Hong; Ngoc, Pham Duc; Hanh, Tran My; Tien, Ngo Anh; Ha, Bui Thi Viet (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract : Hydrogen is considered as an ideal substitute to fossil fuels in the energy and non-polluting characteristics. Biological hydrogen production using microorganisms is a promising method to the world's energy industry. The anaerobic, mesophilic, Gram-positive strain Clostridium beijerinckii CB3 ( C. beijerinckii CB3) isolated from cattle feces in North of Vietnam has been studied to optimize the biohydrogen production in anaerobic condition. In this study, the effects of culture conditions on hydrogen production by C. beijerinckii CB3 were investigated in batch culture using serum bottles. Various medium components (carbon and nitrogen sources, inorganic salts) and environmental factors (initial pH, temperature of incubation), time and orbital shaker of culture were optimized for hydrogen production by C. beijerinckii CB3. The optimal parameters for the best growth and biohydrogen production in batch tests were incubation time 48 h, 37 o C, pH 8.5, and orbital shaker 200 rpm. The maximum cell growth of 1.6 in OD 600 and biohydrogen production of 881.25 mL/L were obtained, respectively, in the medium containing 10 g/L of glucose, 10 g/L of yeast extract or 10 g/L of peptone, 480 mL/L of NaHCO 3 , and 32 mL/L of K 2 HPO 4 . These results indicated that C. beijerinckii CB3 is a potential candidate for fermentative biohydrogen production. Keywords: Biohydrogen production, C. beijerinckii , culture condition, growth, anaerobic condition.